Sosialisasi Vaksinasi COVID-19 Populasi Khusus Bagi Civitas Akademia dan Hospitalia Universitas Mataram dalam Rangka Dies Natalis Universitas Mataram Ke-59 Tahun 2021 - Eustachius Hagni Wardoyo; Didit Yudhanto; Linda Silvana Sari; Titi Pambudi Karuniawaty; Triana Dyah Cahyawati (Universitas Mataram, 2022)
The national COVID-19 vaccination kick-off will begin on January 13, 2021, starting with the vaccine given to President Joko Widodo. The COVID-19 vaccination program has been running for 11 months and is still causing pros and cons in the community regarding its acceptance. The pros and cons, mainly targeting the special population, namely pregnant women, breastfeeding mothers and children still trigger doubts. The socialization of COVID-19 vaccination in this special population needs to be given to the community, starting from the educators represented by the academia and hospitalia members of the University of Mataram. This socialization was attended by 132 participants through a zoom meeting. Discussions related to the pathophysiology of COVID-19, how the COVID-19 vaccination protection is formed and how long, and also the prevention of COVID-19 have been well answered by the resource persons. One of the ways to respond to offline learning that has been answered is to speed up the vaccination program for school-age children, which starts at the age of junior-high school (12-17 years) and immediately follows the elementary age (6-11 years)